Correlation between Working Postures and The Complaints of Musculoskeletal Diseases of The Fishermen in Tanjung Village, Sumenep District - Nefri Daika (Universitas Airlangga, 2019)
Introduction: The working activities of the fishermen in Tanjung Village are still considered as traditional works providing the works are done manually with non-ergonomic working postures, such as bending, standing, squatting, and legs bending. Accordingly, these postures trigger the complaints of musculoskeletal diseases (MSDs). Musculoskeletal diseases are diseases in the skeletal muscles, for example, pains, aches, pins and needles, and heat. Working as a fisherman means that one dedicates half of her/his time to catch fish mostly by using traditional boats and equipment. Thus, a lot of fishermen are discovered complaining about pains after completing their work. This research aims to distinguish the relationship among variables. Methods: This research is observational research that applies the cross-sectional design. The research samples as many as 56 fishermen are chosen by implementing the cluster random sampling technique. The data are obtained by completing measurements, interview, and observation by applying the Rapid Entire Body Assessment (REBA) method and by distributing the Nordic Body Map (NBM) questionnaires. Results: As many as 73.2% of the fishermen have a high risk of musculoskeletal diseases and 46.4% have been working in high-risk working postures. Conclusion: The working postures have a weak relationship (r=0.407) with the complaints of musculoskeletal diseases. Keywords: fishermen, complaints of musculoskeletal diseases, Nordic Body Map, Rapid Entire Body Assessment